The documentary genre and the development of types of audiovisual literacy in ibero-american communication faculties - Karbaum Padilla, Gerardo (2025)
Media literacy, or educommunication, has audiovisual literacy as one of its dimensions. This has always been promoted for application in schools and civil society, however, there are not many studies on its application in the university setting. Therefore, this research aims to study audiovisual literacy applied in communication faculties in Latin America through the teaching of the documentary genre. A qualitative approach was used through semi-structured interviews with teachers from educational institutions in nine countries in the region. The results obtained show that, although curricula do not explicitly address it, teachers and students carry out this literacy at different levels and depths, which is why an initial typology is proposed consisting of audiovisual literacy: by genre, intergeneric, transversal, and instrumental.